POST OPERATIVE OUTCOMES OF OPEN VERSUS CLOSED HAEMORRHOIDECTOMY - Hadi, Ain ul; Khan, Shehzad Akbar; Aman, Zahid (Journal of Postgraduate Medical Institute, 2011)
Objective: Methodology: nd, 3rd and 4th Results: The mean age of the sample was 45.5±2.3 years. In group B, 08 (32%) patients had mild pain, 10 (40%) had moderate and 02 (08%) had sever pain post operatively as compared to 13 (52%) patients with mild, 11(44%) with moderate and 06 (24%) with severe pain in group A (p < 0.05). Similarly early post operative bleeding was noted in 15 (60%) patients in group A and 06 (24%) patients in group B (p < 0.05). Wound healing time was just over 02 weeks in group B as compared to more than 04 weeks in group A (p < 0.05). Conclusion: degree haemorrhoids. Closed haemorrhoidectomy technique is much better than open technique for 2nd, 3rd and 4 th degree haemorrhoids having no systemic illnesses were included in this study. Patients were randomly divided in two equal groups. Group A included patients undergoing open haemorrhoidectomy and group B catered for patient with closed haemorrhoidectomies. Post operatively these patients were followed up in the OPD for 02 months and were evaluated for post operative pain, bleeding and wound healing in addition to other complications like urinary retention and anal fissure. This experimental study was carried out in the surgical unit, at Hayatabad Medical Complex Peshawar from March to August 2009. Fifty patients of 2 To compare the therapeutic results of open haemorrhoidectomy with closed one in terms of post operative pain, bleeding and wound healing.